Interethnic Marriage and Identity Confusion: a Phenomenological Study - Sarah Priliyanti; Muhammad Yusuf Taujiri; Naufal Nur Ihsan; Putri Khairunisa; Fridayanti Fridayanti (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
This study aims to explore the experiences of children resulting from intercultural marriages in Indonesia and the factors that influence the emergence of confusion about their cultural or ethnic identity. The approach used is qualitative with phenomenological design. The research subjects were selected based on purposive sampling techniques at students of a high school in the city of Bandung. Data were collected through interview techniques and processed using methods used by Giorgi (1985). The emerging themes are categorized and interpreted, taking into account the research questions and theoretical frameworks used. The results showed that some informants experienced confusion, and others did not. The factors identified influencing the appearance of confusion are adaptation, parenting communication and their social envirentment which their live.